A comparison of methods for the detection of Phytophthora infestans on potatoes in Mauritius : Detection of Phytophthora infestans - Sanmukhiya, Mala; Takooree, Sandhya Devi; Neetoo, Hudaa; Vally, Vivian; Bulajić, Aleksandra; van der Waals, Jacquie (Journal of Agricultural Sciences (Belgrade), 2022)
Late blight, a disease caused by oomycota, Phytophthora infestans, is a greater threat to the potato crop than any other disease in Mauritius. This disease remains the most challenging to manage once symptoms have appeared, thus warranting rapid detection for effective disease management. The aim of this study was to compare different methods for early detection of the causal agent of potato late blight. Conventional culture-based methods involved the direct isolation of P. infestans from infected leaves on Carrot Piece Agar (CPA), Carrot Sucrose Agar (CSA), Commercial Potato Dextrose Agar (CPDA), Fresh Potato Dextrose Agar (FPDA-1 and FPDA-2), Oatmeal Agar (OMA), Pea Sucrose Agar (PSA) and Water Agar (WA) without antibiotic supplementation. Mycelial growth on agar was subsequently identified using molecular techniques. A culture-independent method was also attempted whereby total genomic DNA was directly extracted from symptomatic leaves with mycelial growth followed by PCR amplification with ITS 5 / ITS 4 primers and sequencing. The different media ranked in the following decreasing order of performance: PSA >>> CSA ~ FPDA-1 > CPA ~ CPDA ~ OMA, with growth appearing on PSA within 7 days without contamination by background flora. DNA sequencing confirmed the identity of the agent recovered from PSA and from diseased leaves to be P. infestans. Findings of this study point to an optimum nutritive medium for recovering and culturing P. infestans from leaves with foliar blight without the use of antibiotics. Alternatively, a culture-independent method can be used for rapid detection and identification during routine disease surveillance.
Keywords: Late blight, morphology, Pea Sucrose Agar, sequencing